Diffuse myocardial fibrosis following tetralogy of Fallot repair: a T1 mapping cardiac magnetic resonance study. - Kozak, Marcelo F; Redington, Andrew; Yoo, Shi-Joon; Seed, Mike; Greiser, Andreas; Grosse-Wortmann, Lars (Pediatric Radiology, 2014)
Background: Adverse ventricular remodeling after tetralogy of Fallot (TOF) repair is associated with diffuse myocardial fibrosis.Objective: The goal of this study was to measure post-contrast myocardial T1 in pediatric patients after TOF repair as surrogates of myocardial fibrosis.Materials and Methods: Children after TOF repair who underwent cardiac magnetic resonance imaging with T1 mapping using the modified look-locker inversion recovery (MOLLI) sequence were included. In addition to routine volumetric and flow data, we measured post-contrast T1 values of the basal interventricular septum, the left ventricular (LV) lateral wall, and the inferior and anterior walls of the right ventricle (RV). Results were compared to data from age-matched healthy controls.Results: The scans of 18 children who had undergone TOF repair and 12 healthy children were included. Post-contrast T1 values of the left ventricular lateral wall (443 ± 54 vs. 510 ± 77 ms, P = 0.0168) and of the right ventricular anterior wall (333 ± 62 vs. 392 ± 72 ms, P = 0.0423) were significantly shorter in children with TOF repair than in controls, suggesting a higher degree of fibrosis. In children with TOF repair, but not in controls, post-contrast T1 values were shorter in the right ventricle than the left ventricle and shorter in the anterior wall of the right ventricle than in the inferior segments. In the TOF group, post-contrast T1 values of the RV anterior wall correlated with the RV end-systolic volume indexed to body surface area (r = 0.54; r(2) = 0.30; P = 0.0238).Conclusion: In children who underwent tetralogy of Fallot repair the myocardium of both ventricles appears to bear an abnormally high fibrosis burden.